Yet it endures: The persistence of original sin - Barry Eichengreen; Ricardo Hausmann; Ugo Panizza (Graduate Institute of International and Development Studies, 2022)
Notwithstanding announcements of progress, "international original sin" (the denomination of external debt in foreign currency) remains a persistent phenomenon in emerging markets. Although some middle-income countries have succeeded in developing markets in local-currency sovereign debt and attracting foreign investors, they continue to hedge their currency exposures through transactions with local pension funds and other resident investors. The result is to shift the locus of currency mismatches within emerging economies but not to eliminate them. Other countries have limited original sin by limiting external borrowing, passing up valuable investment opportunities in pursuit of stability. We document these trends, analyzing regional and global aggregates and national case studies. Our conclusion is that there remains a case for an international initiative to address currency risk in low- and middle-income economies so they can more fully exploit economic development opportunities.
Keywords: H63; F34; C82; 330; Original sin; Currency mismatches; Debt crises